Vegetation composition and ecological gradients of subtropical-moist temperate Ecotonal forests of Nandiar Khuwar Catchment, Pakistan - Haq, Faizul; Ahmad, Habib; Iqbal, Zafar (Bangladesh Journal of Botany, 2018)
Present study was conducted in the mixed Pinus roxburghii Surgent and Pinus wallichiana A.B. Jackson forests of Nandiar Khuwar catchment Battagram District of Pakistan. The aim of this study was to examine the spatial pattern of vegetation composition and its relationship to microclimatic and edaphic factors. Vegetation sampling was carried out using 12 stands between elevations of 1250 - 2050 m in the study area. Four plant communities were recognized through TWINSPAN classification. Life form was dominated by nanophanerophytes and leaf size spectra were dominated by microphyll. The maximum similarity index value (32.9) was recorded between P. roxburghii, P. wallichiana, Q. incana community and Q. incana, P. roxburghii, P. wallichiana community. In Bray-Curtis ordination, maximum ordination score (0.746) was recorded for axis 1. In DCA ordination, maximum gradient length (2.43) was recorded for axis 1 with eigenvalue 0.35. In CCA ordination, maximum eigenvalue was recorded for axis 1 (0.35). The total variance (inertia) in the species data was 2.15, explanatory variables account for 100%. On axis 1 the maximum correlation (−0.749) and maximum tau value (−0.565) was recorded for wet bulb. On axis 2 the maximum negative correlation value was recorded for temperature (−0.553) and maximum tau value was recorded for slope aspect (−0.480).